THE INFLUENCE OF SOCIAL CIRCUMSTANCES ON THE EMERGENCE OF HARD-BOILED (Heritage, 2022)
The detective genre is based on a narrative that depicts the search for and unraveling of a mysterious offense in a plausible environment. It includes three subgenres (schools): classical, hard-boiled, and metadetective. Each subgenre modifies and harmonizes the mentioned narrative with the socio-ideological horizon to which it belongs. In this paper, the social circumstances that led to the transformation of the narratives of the classical school and the emergence of hard-boiled are observed. This subgenre appeared in America in the 1930s. America was a country in crisis, recession and prohibition caused corruption, unemployment, and crime. This caused the audience to lose confidence in the ability of the individual and feel powerless before the industrial, technological, and political forces of mass society. Hard-boiled, in the form of his detective, offers, compared to that of the classical school, a new model of behavior to restore the shaken trust in personal values. Detectives of this school turn to the primordial male determinant and become a phallus, not only in terms of erectile power, which they constantly prove in fighting, drinking, and sexual adventures but also in the name that became their colloquial determinant - dick (penis). The influence of social circumstances in shaping the hard-boiled school of the detective genre is most noticeable in the role of Black Mask magazine, through which almost all important representatives of this subgenre grew. Black Mask taught the authors to write following the expectations of the audience, as well as "invited" readers to become skilled and well-paid workers, to be men and "rough-and-tumble".
Keywords: detective genre, hard-boiled, (The) Black Mask, narrative, social circumstances